Ensaios em economia do trabalho : uma análise das minorias no mercado de trabalho brasileiro - Bussmann, Tanise Brandão (2017)
The main goal of this thesis is to verify the conditions that some minorities find in the Brazilian Labor Market. Each essay contains a specific minority and it can be read in an independently way. The first essay is about people with disability, which were beneficed by the Brazilian legislation that impose a minimal hiring into companies from the private sector and a minimal reservation vacancy in the public sector in the 1990 decade. It is analyzed the probability of this individual to be working and also the quantity of hours worked, using a logistic model in the first question and a tobit model in the second one. The second essay is about the insertion of black and brown, that were favored with the affirmative action to enter the public sector in some states. In this essay it is used the synthetic control method. The last essay is about the gender differences, were female usually are in a disadvantaged position in wage. In this case, it is analyzed the differentials in the functional position when entering the labor market, which is known as the glass door phenomena, and the wage differentials according to severity, exploring distinct methodologies. The three essays haven the goal to analyze the insertion and the differences that the minorities find in the Brazilian labor market. The results indicate a better insertion and a reduction in the inequalities in the Brazilian labor market.